A One-Year Follow-Up Study on Community Dwelling Multiple Stroke Survivors with Spatial Neglect. Issue 1 (2nd January 2020) - Hreha, Kimberly; Rich, Timothy; Wong, Jennifer
Abstract: This study assessed nine participants, who sustained multiple strokes and had spatial neglect, one year after participation in a prior trial on whether Prism Adaptation Treatment (PAT) was a feasible and effective treatment for spatial neglect remediation compared to standard care. The objectives were to: (1) describe the sample, (2) measure the degree of spatial neglect symptoms if present, and (3) determine group differences in motor and spatial performance. Three (60%) participants from the PAT group and two (50%) from the comparison group still displayed spatial neglect. A series of two-way mixed ANOVAs exploring group (PAT vs. comparison of standard care) and time effects (pretest vs. posttest vs. follow-up) found a main effect of time for all participants on the Kessler Foundation Neglect Assessment (F(1, 2) = 30.28, p<.001), Functional Independence Measure (F(1, 2) = 16.998, p<.001), and star cancelation (F(1, 2) = 11.077, p<.001). An interaction effect of time*prism was observed when assessing the line bisection test (F(1, 2) = 6.986, p = .008), suggesting that the PAT group performed significantly better on this test. Additional research should be completed with a larger sample in order to better understand the PAT long term effects as well as develop clinical recommendations for occupational therapy practitioners.